2008
DOI: 10.1093/ndt/gfn554
|View full text |Cite
|
Sign up to set email alerts
|

The changing spectrum of primary glomerular diseases within 15 years: A survey of 3331 patients in a single Chinese centre

Abstract: The spectrum of primary glomerulonephritis has changed within the last 15 years. The relative frequency of non-IgA MsPGN, EnPGN and MPGN decreased significantly, while that of MCD and IgA nephropathy increased significantly. The relative frequency of FSGS increased significantly in younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
136
6
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(166 citation statements)
references
References 21 publications
21
136
6
3
Order By: Relevance
“…The incidence of MPGN has been reported to decrease over time from about 7-10% in the 1970s to about 2% during 1990-2011 [3][4][5][6][16][17][18][19]. In the present study, among the 26,535 patients with biopsy-confirmed disease, 593 (2.2%) patients were registered as having a histopathology of MPGN types I and III.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…The incidence of MPGN has been reported to decrease over time from about 7-10% in the 1970s to about 2% during 1990-2011 [3][4][5][6][16][17][18][19]. In the present study, among the 26,535 patients with biopsy-confirmed disease, 593 (2.2%) patients were registered as having a histopathology of MPGN types I and III.…”
Section: Discussionmentioning
confidence: 44%
“…In the clinical setting, MPGN is one of the most common causes of nephrotic syndrome in both children and adults, and accounts for approximately 2-10% of all cases of biopsy-confirmed glomerulonephritis [3][4][5][6]. Traditionally, MPGN has been classified based on the findings of electron microscopy as primary MPGN type I (MPGN I), MPGN II, MPGN III, or secondary MPGN [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Along with membranous nephropathy and FSGS, minimal change disease (MCD) is one of the major glomerulonephritides in adult patients with primary nephrotic syndrome (1)(2)(3)(4)(5)(6) and especially common in Asian countries (4)(5)(6). Although few patients with MCD progress to ESRD, a series of studies reported that approximately 30%-70%, most commonly 60%, of adult MCD patients experienced at least one relapse of proteinuria (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and that 50%-60% of patients with a first relapse subsequently experienced a second relapse (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…IgA nephropathy (IgAN) is the most common type of primary GN worldwide [1][2][3] and widely considered to be a polygenic disease. [4][5][6] Although the exact pathogenesis is still unclear, a multihit mechanism has been proposed for IgAN, including at least four hits (production of galactose-deficient IgA1 [Gd-IgA1], production of antiglycan antibodies, formation of IgA1-containing immune complexes, and glomerular injury after mesangial deposition).…”
mentioning
confidence: 99%